2007
DOI: 10.1121/1.2772402
|View full text |Cite
|
Sign up to set email alerts
|

Speech disruption during delayed auditory feedback with simultaneous visual feedback

Abstract: Delayed auditory feedback (DAF) regarding speech can cause dysfluency. The purpose of this study was to explore whether providing visual feedback in addition to DAF would ameliorate speech disruption. Speakers repeated sentences and heard their auditory feedback delayed with and without simultaneous visual feedback. DAF led to increased sentence durations and an increased number of speech disruptions. Although visual feedback did not reduce DAF effects on duration, a promising but nonsignificant trend was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Delayed auditory feedback can result in an increase in speech errors and breakdown in speech fluency (e.g., Jones & Striemer, 2007; Corey & Cuddapah, 2008). The findings from the present study support such earlier reports of increase in errors and disfluencies under delayed auditory feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed auditory feedback can result in an increase in speech errors and breakdown in speech fluency (e.g., Jones & Striemer, 2007; Corey & Cuddapah, 2008). The findings from the present study support such earlier reports of increase in errors and disfluencies under delayed auditory feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Post-lingually deaf individuals display alterations to both segmental and suprasegmental aspects of speech, such as dysfluencies and reduced speech rate (Cowie et al , 1982; Lane and Webster, 1991; Schenk et al , 2003). Studies that manipulate auditory or somatosensory feedback during speech indicate that speakers also modify their speech according to reafferent information (MacKay, 1970; Fabbro and Daro, 1995; Hashimoto and Sakai, 2003; Jones and Striemer, 2007), suggesting at least some degree of influence of sensory feedback during speech. By quantifying behavioural and neural responses to manipulations of sensory feedback during speech motor control, these studies have revealed some of the mechanisms involved in the sensory control of speech (Yates, 1963; Larson et al , 2000; Nasir and Ostry, 2009; Patel et al , 2011; Kort et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…DAF has been proven a powerful method for reducing disfluencies in people who stutter (e.g., Armson & Stuart, 1998;Kalinowski, Armson, Roland-Mieszkowski, Stuart, & Gracco, 1993;Kalinowski, Stuart, Sark, & Armson, 1996;Sparks, Grant, Millay, Walker-Baston, & Hynan, 2002;Van Borsel, Reunes, & Van den Bergh, 2003). In contrast, it typically induces disfluencies and decreases speech rate in normally fluent people but with apparent individual variation (Fabbro & Darro, 1995;Jones & Striemer, 2007;Lee, 1950aLee, , 1950bMacKay, 1970;Stephen & Haggard, 1980;Van Borsel, Sunaert, & Engelen, 2005). These opposing effects of fluency induction in people who stutter and disfluencies in normally fluent adults demonstrate the potency of this manipulation, especially because fluent speakers do not show significant disfluencies under other types of altered auditory feedback.…”
mentioning
confidence: 99%